OPTIMALISASI PENYUSUNAN SILABUS DAN RPP BERBASIS SUPERVISI AKADEMIK UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN - Devika Septiani; Anisah Anisah; Helita Septaria; Ocha Anggraini; Mania Emilia (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
ABSTRACT The development of syllabi and Lesson Plan (Rencana Pelaksanaan Pembelajaran / RPP) constitutes an essential component in supporting effective learning processes and achieving students’ competencies. However, instructional planning practices in schools continue to encounter various challenges, particularly those related to teachers’ pedagogical competence, the implementation of the Merdeka Curriculum, and the limited effectiveness of academic supervision. This study aims to analyze the optimization of syllabus and RPP development based on academic supervision in improving learning quality. The research employed a qualitative approach using a systematic literature review of 28 scientific articles obtained from Google Scholar, Garuda, and SINTA databases published between 2022 and 2026. Data analysis was conducted through identification, selection, categorization, and synthesis stages to identify patterns, trends, and strategies for improving instructional planning. The findings indicate that the quality of syllabi and RPP is strongly influenced by teachers’ ability to formulate learning objectives, strategies, and evaluation systems in an integrated manner. Academic supervision based on coaching and mentoring was found to be more effective in enhancing teachers’ professional competence compared to conventional one-way administrative supervision. In addition, the utilization of artificial intelligence and educational technology provides opportunities to create more adaptive, creative, and contextual learning practices. This study emphasizes that improving the quality of instructional planning requires strengthening teachers’ competencies, collaborative academic supervision, and sustainable integration of educational technology. ABSTRAK Penyusunan silabus dan Rencana Pelaksanaan Pembelajaran (RPP) merupakan bagian penting dalam mendukung efektivitas pembelajaran dan pencapaian kompetensi peserta didik. Namun, praktik perencanaan pembelajaran di sekolah masih menghadapi berbagai kendala, terutama berkaitan dengan kompetensi pedagogik guru, implementasi Kurikulum Merdeka, dan belum optimalnya supervisi akademik. Penelitian ini bertujuan menganalisis optimalisasi penyusunan silabus dan RPP berbasis supervisi akademik dalam meningkatkan kualitas pembelajaran. Penelitian menggunakan pendekatan kualitatif dengan jenis systematic literature review terhadap 28 artikel ilmiah yang diperoleh melalui database Google Scholar, Garuda, dan SINTA pada rentang tahun 2022–2026. Proses analisis dilakukan melalui tahap identifikasi, seleksi, kategorisasi, dan sintesis temuan penelitian untuk menemukan pola, kecenderungan, serta strategi pengembangan perangkat pembelajaran. Hasil penelitian menunjukkan bahwa kualitas silabus dan RPP dipengaruhi oleh kemampuan guru dalam merancang tujuan, strategi, dan evaluasi pembelajaran secara terpadu. Supervisi akademik berbasis coaching dan mentoring terbukti lebih efektif dalam mendukung pengembangan kompetensi guru dibandingkan supervisi administratif yang bersifat satu arah. Selain itu, pemanfaatan artificial intelligence dan teknologi pembelajaran memberikan peluang pengembangan pembelajaran yang lebih adaptif, kreatif, dan kontekstual. Penelitian ini menegaskan bahwa peningkatan kualitas perangkat pembelajaran memerlukan penguatan kompetensi guru, supervisi kolaboratif, dan integrasi teknologi pendidikan secara berkelanjutan.